1999
DOI: 10.1046/j.1463-1318.1999.00043.x
|View full text |Cite
|
Sign up to set email alerts
|

Delays experienced by patients with symptomatic colorectal cancer

Abstract: Despite prompt GP consultation and out-patient referral, delays in the treatment of CRC now occur after referral to hospital. Patients referred without mention of CRC wait longest. Colonoscopy and double contrast barium enema have not improved tumour staging at treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
(12 reference statements)
0
7
1
Order By: Relevance
“…Other studies have also found symptom duration to be longer for rectal cancer than for colon cancer (9,11). In this study the difference disappeared when the emergency group was excluded.…”
Section: Discussioncontrasting
confidence: 38%
See 2 more Smart Citations
“…Other studies have also found symptom duration to be longer for rectal cancer than for colon cancer (9,11). In this study the difference disappeared when the emergency group was excluded.…”
Section: Discussioncontrasting
confidence: 38%
“…Overall, patients' delay in reporting their problems was comparatively short (11,12) but they still expressed a tendency to wait before presenting with symptoms. Patients reported lack of knowledge to be the most important reason for not presenting more promptly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be because when the GP has a clear suspicion, the referral is made more promptly and the response of hospital doctors to this type of referral is faster [44,45]. …”
Section: Discussionmentioning
confidence: 99%
“…An ambitious aim would be to achieve a time lag of up to 4 months before treatment in all patients, allowing 4 weeks from the onset of symptoms to a general practitioner consultation, 2 weeks for general practitioner referral, a 2-week wait for an outpatient appointment, and 6 weeks for diagnosis, staging and treatment. However, average delay can vary between 4 and 9 months [18][19][20][21][22][23][24][25][26][27][28] ( Table 1) and has remained constant for 60 years (Table 2) [18,19,22,23,[29][30][31][32][33][34][35][36][37][38][39][40]. A delay of over 6 months occurs in 30% of patients and of over a year in around 10% ( Table 2).…”
Section: Methods Of Assessing the Evidencementioning
confidence: 99%